Relation of Plasma Renin Activity and Stroke and Heart Attack in the Epidemiological Survey - Goto, Kyoko (Nihon Rōnen Igakkai zasshi, 1978)
In the epidemiological survey for three years, casual plasma renin activity PRA of normotensive and hypertensive subjects older than 40 years was measured using radioimmunoassay. 617 normotensives and 379 hypertensives were measured. Mean value of PRA of normotensives was utilized as one of the three criteria for normal renin group, and the values higher or lower than mean±SD were classified as high or low renin group, respectively. In hypertensive subjects, low PRA was found in 23%, normal PRA in 64%, and high PRA in 13%. The incidence of low PRA in hypertensives was significantly higher in normotensives. PRA was inversely correlated to systolic blood pressure in normotensives and whole subjects including hypertensives throughout three year survey. There was also inverse correlation between PRA and age in normotensives and whole subjects in 1974 year survey. ST and T abnormalities in ECG were found more frequently in hypertensive-high renin group. Among all subjects, there occured 11 strokes and 2 heart attacks during two years. Their PRAs were high in seven patients, low in five and normal in only one. With age-sex matched control, inidence of stroke and heart attack was significantly higher in high and low renin groups than in normal renin group. In high renin group, incidence was also higher than in normal renin group with age-sex-blood pressure matched control. Multivariate analysis revealed that systolic blood pressure and high renin were more important risk factors for stroke and heart attack. It was concluded from this prospective study that there is a relationship between the level of PRA and the incidence of stroke and heart attack, and measurement of casual PRA in epidemiological survey is significant.